„А вы в конец света верите?”. Апокалипсис в современной русской литературе: пророчества индейцев в романе Дмитрия Глуховского „Сумерки" - Szarycz, Ireneusz (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
Dmitry Glukhovsky’s Sumerki (Twilight, 2007) is the story of a young Muscovite who takes up the task of decoding the prophecies of the Maya Indians and connects them with the catastrophes that plague today’s world: earthquakes in Iran, hurricanes in the USA, tsunamis in Indonesia, and drought and conflagrations in Russia. The newspaper headlines and TV news announcements look like Maya Indian prophecies. While translating the old diary of a Spanish conquistador, he becomes involved in a maelstrom of incredible events which will help him interpret the predictions and look into the future, even at the cost of his own life. Can the world be saved? This is the question that Glukhovsky already asked his readers in his previous, dark and apocalyptic science fiction novel Metro 2033 (2005) about a bleak and not-too-distant future. His novel Sumerki is more than a novel – it is rather a metaphor and a manifesto.
“Do you believe in the end of the world?”. The apocalypse in contemporary Russian literature: the Maya Indian prophecy in Dmitry Glukhovsky’s novel “Sumerki” (“Twilight”)
„A wy w koniec świata wierzycie?”. Apokalipsa we współczesnej literaturze rosyjskiej: przepowiednie Majów w powieści Dmitrija Głuchowskiego „Sumierki” („Zmierzch”)